2011
DOI: 10.1073/pnas.1010194108
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the determinants of selectivity in drug metabolism through modeling of dextromethorphan oxidation by cytochrome P450

Abstract: Cytochrome P450 enzymes play key roles in the metabolism of the majority of drugs. Improved models for prediction of likely metabolites will contribute to drug development. In this work, two possible metabolic routes (aromatic carbon oxidation and O-demethylation) of dextromethorphan are compared using molecular dynamics (MD) simulations and density functional theory (DFT). The DFT results on a small active site model suggest that both reactions might occur competitively. Docking and MD studies of dextromethor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 55 publications
10
87
0
2
Order By: Relevance
“…Geometry optimizations in proteins are well known to suffer from being trapped in some of the myriads of local minima, and free energy calculations are necessary for more quantitative results. [62][63] Here we tested whether our minimized pathways correspond to the ones obtained by dynamical trajectories. We initiated random downhill trajectories from near the transition states for the WT enzyme and the T138Stop mutant, starting from different thermally equilibrated classical regions.…”
Section: Downhill Trajectoriesmentioning
confidence: 99%
“…Geometry optimizations in proteins are well known to suffer from being trapped in some of the myriads of local minima, and free energy calculations are necessary for more quantitative results. [62][63] Here we tested whether our minimized pathways correspond to the ones obtained by dynamical trajectories. We initiated random downhill trajectories from near the transition states for the WT enzyme and the T138Stop mutant, starting from different thermally equilibrated classical regions.…”
Section: Downhill Trajectoriesmentioning
confidence: 99%
“…However, in the present study, in order to approximate to a sufficient amount of sampling, QM/MM potential energy profiles have been calculated using three randomly chosen structures derived from the last nanosecond of the 2 ns long MD trajectory similarly to other studies. 86,98,99 These starting structures were snapshots of the enzyme, thus differed in many minor details which could arise due to thermal motion of the atoms. A very important difference from the QM/MM study published earlier 26 was that we observed no hydrogen bond between the side chain of Thr 310 and the formyl group of the substrate during the entire length of the MD simulation, since the catalytic water molecule remained between the Thr 310 side chain and the Fe-O moiety forming hydrogen bonds to both of them.…”
mentioning
confidence: 99%
“…It was reported that aspirin was a CYP 2C9 substrate and inducer (2). A recent study utilized computer simulation to investigate dextromethorphan oxidation by cytochrome P450 at the atomic level (17). Dextromethorphan was found to be oxidized by the heme group of the active site of CYP 2D6.…”
Section: Discussionmentioning
confidence: 99%